ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PENGGUNAAN INFORMASI AKUNTANSI BERBASIS E- COMMERCE PADA UMKM - Anis Nur Jannah (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2021)
The purpose of this research is to find out statistical information, business turnover, preparation and presentation of financial reports on the use of e-commerce-based accounting information at MSMEs in Ngemplak District, Boyolali Regency. The approach is used as an approach to quantitative research. The data used in this research is primary data which comes from the questionnaires that have been distributed. The sample in the study was 97 respondents. The method used in determining respondents using the Slovin formula, with the sampling technique used is probability sampling. Data processing used SPSS 19 implication software. The data analysis used was validity and reliability test, classical assumption test and hypothesis test. Based on the results of the research, hypothesis testing using the test shows that the variable influence of accounting knowledge, the preparation and presentation of financial statements partially has a significant positive effect on the use of e-commerce-based accounting information.